Incidence of Medically Compromised Patient’s attending Oral Surgery Department for Extraction and Minor Surgery - Bokhari, Syed Kamran (International Journal of Psychosocial Rehabilitation, 2014)
Objectives:Minor Oral Surgery and Teeth Extraction in medically compromised patients need special care and care. Aim of this study was to analyse the incidence of medically compromised patients attending oral surgery department for teeth extraction and minor oral surgery.Materials and Methods:Patients with medically compromised conditions were sub-divided into. This study was conducted with the following aim & objectives: 1.To assess the incidence of medical conditions in patients 2. To assess the type of medical condition and age group 3. To estimate the statistical significance and compare with similar studies.Results: Diabetes mellitus was the most common Co morbidity Affecting the people which was found to be statistically significant (p=